Effects on reactivity with feedback tempearture (2024)
Different numerical simulations for the calculation of reactivity with feedback temperature effects are presented in this work. The Euler-Maclaurin series approximation with the second Bernoulli number is considered to discretize the inverse point kinetic equations. The Doppler effect is considered in dependence on the feedback temperature, which is recursively calculated from an initial value. Different numerical experiments with different computational time steps, simulation times, and neutron population density shapes are performed to validate the proposed method.